Clinical swallowing prognostic indicators in patients with acute ischemic stroke - Karoline Kussik de Almeida LEITE; Fernanda Chiarion SASSI; Gisele Chagas de MEDEIROS; Luiz Roberto COMERLATTI; Claudia Regina Furquim de ANDRADE (Arquivos de Neuro-Psiquiatria)
ABSTRACT A swallowing disorder is present in more than 50% of patients with acute stroke. Objective To identify clinical prognostic indicators of the swallowing function in a population with acute ischemic stroke and to determine prioritization indicators for swallowing rehabilitation. Methods Participants were adults admitted to the emergency room who were diagnosed with acute ischemic stroke. Data gathering involved a swallowing assessment to determine the functional level of swallowing (American Speech-Language-Hearing Association National Outcome Measurement System – ASHA NOMS) and the verification of demographic and clinical variables. Results The study sample included 295 patients. For analysis purposes, patients were grouped as follows: ASHA NOMS levels 1 and 2 – ASHA1 (n = 51); levels 3, 4 and 5 – ASHA2 (n = 96); levels 6 and 7 – ASHA3 (n = 148). Statistical analyses indicated that patients who presented a poorer swallowing function (ASHA1) were older (age ≥ 70 years); had anterior circulation infarct; had lower scores on the Glasgow Coma Scale (GCS ≤ 14 points); took longer to initiate swallowing rehabilitation; had longer hospital stays; made more use of alternative feeding methods; needed more sessions of swallowing rehabilitation to remove alternate feeding methods; took longer to return to oral feeding and had poorer outcomes (fewer individuals discharged from swallowing rehabilitation sessions and increased mortality). Conclusion Patients with acute ischemic stroke, admitted to the emergency room, aged ≥ 70 years, score on the GCS ≤ 14, anterior circulation infarct and dementia should be prioritized for swallowing assessment and rehabilitation.